“A Global City in a Global Pandemic: Assessing the Ongoing Impact of COVID Induced Trends on London's Economic Sectors” - Dylan Anderson; Rachel Hesketh; Mark Kleinman; Jonathan Portes (Global Labor Organization (GLO), 2020)
Over the last 50 years, London has successfully adapted to technological change and globalization, making it the major driver of the UK economy. But its strengths have also made the city particularly vulnerable to the health impacts of COVID-19, and potentially also to wider negative economic implications of the crisis. Many of London's key sectors rely on proximity, agglomeration economies and externalities. We evaluate the available data on the impact of the pandemic on London to date, with a particular focus on the differential effects between sectors. We also identify seven key trends, affecting both the demand and supply side of the economy, that are likely to have significant medium- to long-term economic impacts, and assess the potential impacts on London's major industrial sectors. Our findings suggest that COVID-19 may further accentuate the existing divide between globally competitive advanced producer services and more locally focused sectors providing lower-value personal and household services, posing a number of significant policy challenges.
Keywords: J11; J24; J61; R11; 330; COVID-19; London; agglomeration economies; migration; services